Zotero Reference Management: A Handbook. - Library, MIE; Conneally, Clare; Patton, Trish (Marino Institute of Education Library, 2022)
This handbook provides an overview of the Zotero reference management tool and how to use it. Zotero is a free, easy-to-use tool to help you collect, organize, cite, and share research. It is a type of reference management software, which you can use to assist you in referencing correctly in your essays.
Keywords: Educational Resource; Library Support; Zotero; Referencing; Reference Management; Handbook; Academic Skills